Islamic Art at The Art Gallery of South Australia - Bennett, James (SUHUF, 2009)
OVER the past ten years, Australia has increasingly aware of Muslim cultures yet today there is still only one permanent public display dedicated to Islamic art in this country. Perhaps it is not surprising that the Art Gallery of South Australia in Adelaide made the pioneer decision in 2003 to present Islamic art as a special feature for visitors to this art museum. Adelaide has a long history of contact with Islam. Following the Art Gallery’s establishment in 1881, the oldest mosque in Australia was opened in 1888 in the city for use by Afghan cameleers who were important in assisting in the early European colonization of the harsh interior of the Australian continent